Isometric hand grip strength measured by the Nintendo Wii Balance Board – a reliable new method. Issue 1 (December 2016) - Blomkvist, A.; Andersen, S.; de Bruin, E.; Jorgensen, M.
Abstract Background Low hand grip strength is a strong predictor for both long-term and short-term disability and mortality. The Nintendo Wii Balance Board (WBB) is an inexpensive, portable, wide-spread instrument with the potential for multiple purposes in assessing clinically relevant measures including muscle strength. The purpose of the study was to explore intrarater reliability and concurrent validity of the WBB by comparing it to the Jamar hand dynamometer. Method Intra-rater test-retest cohort design with randomized validity testing on the first session. Using custom WBB software, thirty old adults (69.0 ± 4.2 years of age) were studied for reproducibility and concurrent validity compared to the Jamar hand dynamometer. Reproducibility was tested for dominant and non-dominant hands during the same time-of-day, one week apart. Intraclass correlation coefficient (ICC) and standard error of measurement (SEM) and limits of agreement (LOA) were calculated to describe relative and absolute reproducibility respectively. To describe concurrent validity, Pearson's product–moment correlation and ICC was calculated. Results Reproducibility was high with ICC values of >0.948 across all measures. Both SEM and LOA were low (0.2-0.5 kg and 2.7-4.2 kg, respectively) in both the dominant and non-dominant hand. For validity, Pearson correlations were high (0.80-0.88) and ICC values were fair to good (0.763-0.803). Conclusion Reproducibility for WBB was high for relative measures and acceptable for absolute measures. In addition, concurrent validity between the Jamar hand dynamometer and the WBB was acceptable. Thus, the WBB may be a valid instrument to assess hand grip strength in older adults.